Gibbon's antagonism to Christianity - McCloy, Shelby Thomas (Williams & Norgate, 1933)
Gibbon's antagonism to Christianity, as seen in his writings.--The Oxford replies to Gibbon.--The Cambridge replies to Gibbon.--Other contemporary assaults--Protestant rejoinders since Gibbon's day.--Catholic challenges since Gibbon's day.--Polemical and other editions of Gibbon.--Rationalist defences and concessions